Pitfalls in clinical genetics - Hui-Lin Chin; Denise Li Meng Goh (Singapore Medical Journal)
With the increasing availability of genetic tests, more doctors are offering and ordering such tests for their patients. Ordering a genetic test appears to be a simple process of filling in paperwork, drawing 3 mL of blood in an ethylenediaminetetraacetic acid tube and receiving a test report. This is identical to sending off a full blood count. However, it is far more complex than that. There are many potential pitfalls, as shown by the increasing number of complaints and lawsuits filed against doctors and allied health staff. Furthermore, clinical genetics involves more than just ordering tests; in fact, focusing on genetic tests alone is a potential pitfall. In this review, we discuss the common pitfalls in clinical genetics and how doctors can avoid these pitfalls to ensure patient safety and to safeguard their practice.